Sapana Tourism Development Strategy Bonto Salama Village, Sinjai Barat District Sapana Tourism Development Strategy Bonto Salama Village, Sinjai Barat Dist - Syarifuddin, Syarifuddin (Devotion : Journal of Research and Community Service, 2022)
In this study, this study aims to determine the trend of the development of greeting tourism and the cultivation of tilapia and carp. The methods used are survey and interview methods. The results showed that the development of sapana tourism in the last two years and in the future is increasing, while the cultivation of tilapia and gouramy has developed and has natural potential in the form of natural beauty surrounded by mountains and has adequate facilities and infrastructure such as a lesehan casebo or restaurant and restaurant. worship place. accessibility of both private and public transportation and local government support. Meanwhile, future linkages from the development of greeting tourism include the addition of tourist attractions such as tilapia cultural tourism or bathing places. Furthermore, the development chain of greeting tourism in the future is an increase in the number of tourist visits along with the development of superior or culinary products so that they can attract tourists to visit. The development of greeting tourism in the future will also open up new job opportunities to meet the needs of tourists while in Bonto Salama village. From the development of greeting tourism, it will also increase people's income from the tourism business that is run and increase regional income from levies imposed on tourists.